Diurnal variations in the quality of stroke care in Sweden. (14th May 2019) - Darehed, David; Blom, Mathias; Glader, Eva‐Lotta; Niklasson, Johan; Norrving, Bo; Bray, Benjamin D.; Eriksson, Marie
Abstract : Objectives: A recent study of acute stroke patients in England and Wales revealed several patterns of temporal variation in quality of care. We hypothesized that similar patterns would be present in Sweden and aimed to describe these patterns. Additionally, we aimed to investigate whether hospital type conferred resilience against temporal variation. Materials and Methods: We conducted this nationwide registry‐based study using data from the Swedish Stroke Register (Riksstroke) including all adult patients registered with acute stroke between 2011 and 2015. Outcomes included process measures and survival. We modeled time of presentation as on/off‐hours, shifts, day of week, 4‐hour, and 12‐hour time blocks. We studied hospital resilience by comparing outcomes across hospital types. Results: A total of 113 862 stroke events in 72 hospitals were included. The process indicators and survival all showed significant temporal variation. Door‐to‐needle (DTN) time within 30 minutes was less likely during nighttime than daytime (OR 0.50; 95% CI 0.41‐0.60). Patients admitted during off‐hours had lower odds of direct stroke unit (SU) admission (OR 0.72; 95% CI 0.70‐0.75). 30‐day survival was lower in nighttime vs daytime presentations (OR 0.90, 95% CI 0.84‐0.96). The effects of temporal variation differed significantly between hospital types for DTN time within 30 minutes and direct SU admission where university hospitals were more resilient than specialized non‐university hospitals. Conclusions: Our study shows that variation in quality of care and survival is present throughout the whole week. We also found that university hospitals were more resilient to temporal variation than specialized non‐university hospitals.